PENINGKATAN MUTU LULUSAN MELALUI PENCAPAIAN KOMPETENSI KLINIK MAHASISWA DIII KEPERAWATAN - Catur Budi Susilo (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2014)
ABSTRACTTo achieve quality nurses, it is an effort to change attitudes and behaviors of the students for the purpose of education. The purpose of education is to prepare curriculum must fit with the skills to reach refer to established standards. The question is whether clinical competence achieved so far is enough for the parameters of quality of graduates? One strategy is to  observe and assess the attainment of competencies in education. With achieving the competition into account, manager of higher education can do political allocation resources for learning, methods, and targets of clinical competence in order to achieve student competence.